THE ROLE OF SYSTEMATIC CONTROL AND EVALUATION SYSTEMS IN IMPROVING THE EFFECTIVENESS OF PUBLIC POLICY: A LITERATURE REVIEW - Sunnah Sunnah; Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the role of systematic control and evaluation systems in improving the effectiveness of public policy through a literature review method. Control systems are seen as mechanisms that ensure policy implementation is in line with plans, prevent deviations, and maintain accountability. Meanwhile, systematic evaluation plays a role in providing data-based assessments of the relevance, effectiveness, efficiency, and impact of policies, while also providing constructive feedback for future policy improvements. The study findings indicate that the integration of these two mechanisms creates a continuous learning cycle that strengthens the policy formulation and implementation processes. Thus, the consistent, adaptive, and evidence-based application of control and evaluation systems is key to achieving effective, transparent, and accountable public policy governance.